Cystadenoma of the pancreas - Albo Volonté, Manuel; Piovano de Lista, Sélika; Cardozo, Tabaré (Cirugía del Uruguay, 1973)
A case of cystadenome of the pancreas is reported, a rare tumor especially when located in the head of the visu. On examination this tumor, aswell as the. great majority of the cases quoted from the literature, was very large. Surgical treatment employed was cephalic duodenopancreatectomy. Histological and oncological basis of this procedure are considered. Bibliography was reviewed. Technical hazards are outlined. The histological data are presented.